PENGARUH FINANCING DEPOSITE RATIO (FDR), CAPITAL ADEQUACY RATIO (CAR), DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA BANK SYARIAH MANDIRI TAHUN 2013-2017 - Luluk Anggraeni; Mr. Mushawir (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2018)
The purpose of this research is to examine the influence of Capital Adequacy Ratio (CAR), Financing Deposit Ratio (FDR), and Operational Cost of Operating Income (ROOP) to Bank Syariah Mandiri The sample in this research is obtained by purposive sampling The criteria of the banks collected in this study are the Financial Statements of the End of the Month of the Month (March, June, September, and December) for the years 2013-2016 and the Final Financial Statements of the Quarterly Months (March, June, and September) for 2017 at Bank Syariah Independent. Result of t test show that CAR variable obtained by regression coefficient equal to -0,753 with significance value equal to 0,463 so that CAR have no effect to ROA. FDR obtained regression coefficient of 1,500 with a significance value of 0.154 so that FDR does not affect the ROA. BOPO obtained regression coefficient of -10.663 with a significance value of 0.000 so that significant effect on ROA. F test results show that CAR, FDR, and BOPO variables simultaneously affect the ROA is indicated with a significance value of less than 0.05 is 0.000. The result of RÂ² test shows that the predictive ability of four independent variables (CAR, FDR, BOPO, ROA) is 96.30%, while the rest of 3.70% is influenced by factors not examined in this research.Keywords:Â Financing Deposite Ratio (FDR), Capital Adequacy Ratio (CAR), Biaya Operasional Pendapatan Operasional (BOPO) dan Return On Asset (ROA)Â